TỔNG HỢP NANO BẠC BẰNG PHƯƠNG PHÁP NỔ - Nhiệm, Đào Ngọc; Yang, Sangsun (Vietnam Journal of Chemistry, 2012)
The technology of wire explosion has been used to produce nanopowders [1, 4, 5, 8, 9]. A new concept was proposed to produce nanosized powder, which is wire explosion in liquid media. We have exploded the Ag wires with 0.1 to 0.3 mm diameter, in the de-ionized water. Electrical energy of 1.1 kJ was stored in a 10-uF capacitor and released to the wires through a triggered spark gap switch. As a consequence, there were no micrometer size particles in the powder, which is attributed to the complete vaporization of the wire. It is considered that the wire explosion in liquid medium meets three conditions to form smaller particles, namely, higher energy deposition in the wire, sufficient expansion volume, and quick cooling of the particles.